At the Centre of Whitehall - Lee, J. author. aut Link
VIII, 299 p.
Keywords: This authoritative text examines the arrangements at the centre of Whitehall for advising the British prime minister and Cabinet, especially during the Thatcher and Major governments. The traditional coordinating centre has shifted from the Treasury to the Prime Minister's Office and the Chief Whip's Office in Downing Street, and to the Cabinet Office in Whitehall. Exploration of the separate but interlinking contributions made by these three parts of the centre shows they form a flexible but not entirely adequate support for modern government.